Feminist Dilemmatic Theorizing: New Materialism in Communication Studies - Harris, Kate Lockwood (Communication theory, 2016)
Feminist communication scholars often adopt seemingly incommensurate stances to navigate tensions among agency, discourse, materiality, and history. I argue that valuing these “contradictions” is a hallmark of feminist communication research, a tradition I label feminist dilemmatic theorizing. Because feminists seek to describe and transform the world, they employ constitutive and representative understandings of communication. Rather than assert these approaches as paradoxical, I reread existing scholarship for nascent feminist new materialisms. Using sexual violence as an example, I argue that feminist communication theory develops a distinct approach to the force of communication, one in which discourse is not all‐powerful. Accordingly, I suggest communication theorists draw upon existing feminist scholarship to meet critiques of social construction and develop a material turn.